2010
DOI: 10.1111/j.1365-3040.2009.02099.x
|View full text |Cite
|
Sign up to set email alerts
|

Root cortical aerenchyma improves the drought tolerance of maize (Zea mays L.)

Abstract: Root cortical aerenchyma (RCA) reduces root respiration in maize by converting living cortical tissue to air volume. We hypothesized that RCA increases drought tolerance by reducing root metabolic costs, permitting greater root growth and water acquisition from drying soil. To test this hypothesis, recombinant inbred lines with high and low RCA were observed under water stress in the field and in soil mesocosms in a greenhouse. In the field, lines with high RCA had 30% more shoot biomass at flowering compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
270
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(283 citation statements)
references
References 49 publications
10
270
1
2
Order By: Relevance
“…Chimungu et al (2014) and Jaramillo et al (2013) reported that larger cells of the root cortical parenchyma reduce cellular respiration in this region, contributing to the deepening of the root system due to a lower metabolic cost, and that corn plants with lower cortex have higher drought tolerance, due to the smaller number of cell rows. Aerenchyma in corn roots may have the function of supporting a greater soil and water acquisition, since these structures decrease the metabolic cost of growing roots because of the reduced presence of cells in respiration (Zhu et al, 2010;Souza et al, 2013). Therefore, the greater root system observed in the tolerant hybrid may be attributed to a higher proportion of aerenchyma in the cortex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimungu et al (2014) and Jaramillo et al (2013) reported that larger cells of the root cortical parenchyma reduce cellular respiration in this region, contributing to the deepening of the root system due to a lower metabolic cost, and that corn plants with lower cortex have higher drought tolerance, due to the smaller number of cell rows. Aerenchyma in corn roots may have the function of supporting a greater soil and water acquisition, since these structures decrease the metabolic cost of growing roots because of the reduced presence of cells in respiration (Zhu et al, 2010;Souza et al, 2013). Therefore, the greater root system observed in the tolerant hybrid may be attributed to a higher proportion of aerenchyma in the cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Morphoanatomical changes in the canopy and root system are involved in mechanisms for efficient water absorption and conservation, and the identification of such mechanisms is crucial for the selection of genotypes tolerant to drought (Zhu et al, 2010;Ge et al, 2012). In corn, it has been shown that greater root length (Ali et al, 2016) and fewer lateral roots (Zhan et al, 2015) lead to an increase in drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Burton et al, (2013) reported that maize landraces have greater variation in root architectural traits and have longer nodal roots and larger xylem than related wild Zea species. Longer roots were shown to assist in the capture of mobile resources in the soil and are considered to be a primary determinant of drought tolerance in maize (Ribaut et al, 2009;Zhu et al, 2010). However, moderate water stress in the field, significantly increased root length.…”
Section: Biomass Partitioning Under Greenhouse Conditionsmentioning
confidence: 99%
“…Root cortical phenes are important for plant performance, particularly under edaphic stress (Zhu et al 2010;Chimungu et al 2014a;Chimungu et al 2014b;Saengwilai et al 2014;Schneider et al 2017b). Root phenes that reduce root metabolic costs including RCS, RCA, cortical cell file number, and cortical cell size reduce carbon and nutrient costs for soil exploration (Chimungu et al 2014a;Lynch et al 2014;Saengwilai et al 2014;Chimungu et al 2014b;Schneider et al 2017a).…”
Section: Rcs and Nutrient Remobilizationmentioning
confidence: 99%
“…Cortical phene states that reduce living cortical tissue reduce root respiration and nutrient content, thereby permitting greater resource allocation to other plant functions including growth and reproduction Lynch 2015). For example, the development of root cortical aerenchyma (RCA) in maize improves plant performance in environments with suboptimal nutrient and water availability (Zhu et al 2010;Postma and Lynch 2011a, b;Jaramillo et al 2013;Saengwilai et al 2014;Chimungu et al 2015), an effect which modeling studies show can be attributed to a reduction in root metabolic costs (Postma et al 2014;Dathe et al 2016). Fewer cell files or greater cell size in the root cortex of maize substantially reduces root respiration and improves soil exploration and water acquisition in conditions of suboptimal water availability (Chimungu et al 2014a(Chimungu et al , 2014b.…”
mentioning
confidence: 99%